A Mini Review of Plant Tissue Culture: The Role of Media Optimization, Growth Regulators in Modern Agriculture, Callus Induction and the Applications - Norrizah Jafaar Sidik; Hasan M. Agha; Abdulmutalib Alabeed Alkamil; Muneer Mohammed Saleh Alsayadi; Amjad Abdulhadi Mohammed (AUIQ Complementary Biological System)
Plant tissue culture is an innovative biotechnological approach developed to meet the escalating global demand for agricultural production with enhanced nutritional value. This aseptic, in vitro technique allows for the cultivation of plant cells, tissues, or entire plants under controlled environmental and nutritional conditions, facilitating the generation of genetically identical clones. The method is indispensable in preserving endangered plant species, boosting crop yield and quality, and enabling year-round production of disease-free plants. Central to plant tissue culture is the composition of the growth medium, which must include a precise balance of macronutrients, micronutrients, amino acids, vitamins, and plant growth regulators such as auxins, cytokinins, gibberellins, and abscisic acid. Recent advancements have fine-tuned media formulations to better accommodate the needs of various plant species. The review highlights the significance of selecting appropriate growth regulators and media types to optimize outcomes, such as callus induction, shoot and root regeneration, and large-scale micropropagation. Furthermore, applications extend beyond agriculture, as tissue culture techniques are pivotal in bioremediation, secondary metabolite production, and plant-based